2021
DOI: 10.18632/oncotarget.27988
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-epigenetic function of the histone methyltransferase KMT2D and therapeutic opportunities for the treatment of KMT2D-deficient tumors

Abstract: Epigenetic mechanisms are central to understanding the molecular basis underlying tumorigenesis. Aberrations in epigenetic modifiers alter epigenomic landscapes and play a critical role in tumorigenesis. Notably, the histone lysine methyltransferase KMT2D (a COMPASS/ Set1 family member; also known as MLL4, ALR, and MLL2) is among the most frequently mutated genes in many different types of cancer. Recent studies have demonstrated how KMT2D loss induces abnormal epigenomic reprograming and rewires molecular pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 89 publications
0
32
0
Order By: Relevance
“…Antisense lncRNAs located in the nucleus can recruit DNA, histone-modifying enzymes, or transcription factors to specific sites to cis-regulate the expression of sense mRNAs ( 53 ). Our study demonstrated that MLL2, a member of the MLL family and a component of the ASC-2/NCOA6 complex (ASCOM), has histone methylation activity and thus participates in transcriptional activation ( 54 ). The FOXP4-AS1 located in the nucleus could increase the expression of FOXP4 by interacting with MLL2.…”
Section: Discussionmentioning
confidence: 96%
“…Antisense lncRNAs located in the nucleus can recruit DNA, histone-modifying enzymes, or transcription factors to specific sites to cis-regulate the expression of sense mRNAs ( 53 ). Our study demonstrated that MLL2, a member of the MLL family and a component of the ASC-2/NCOA6 complex (ASCOM), has histone methylation activity and thus participates in transcriptional activation ( 54 ). The FOXP4-AS1 located in the nucleus could increase the expression of FOXP4 by interacting with MLL2.…”
Section: Discussionmentioning
confidence: 96%
“…As the largest H3K4 methyltransferase among them, KMT2D also represents the most frequently mutated gene in multiple human cancers, including OSCC [ 1 , 2 , 8 ]. Nonetheless, the role of KMT2D in tumor development remains largely controversial [ 8 , 9 ]. Using a gene-editing mouse model, Dhar and Alam showed that tissue-specific ablation of Kmt2d in the brain and lung promoted tumorigenesis [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of chromatin modifiers, histone-lysine N -methyltransferase 2D (KMT2D) is among the most frequently mutated genes in multiple human cancers, including OSCC [ 8 , 9 ]. The Cancer Genome Atlas Network (TCGA) revealed that the mutation frequency of KMT2D in head and neck squamous cell carcinoma (HNSCC) was 18% among 279 HNSCC patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevailing hypothesis is that alterations in KMT2 function contribute to carcinogenesis through the modification of histone methylation patterns; thus, novel therapeutic agents targeting other histone demethylases may be an option to inhibit disease recurrence and/or progression in tumors with KMT2D alterations [35,36]. Given that the data from UTUC patients from the TCGA show that KMT2D alterations are co-expressed with fibroblast growth factor receptor (FGFR3) alterations in more than half of the cases, a plausible treatment strategy may also be a combination of FGFR3 inhibitors with histone demethylase inhibitors [37].…”
Section: Discussionmentioning
confidence: 99%